Problem-Based Learning Effect on Elementary Students Critical Thinking with Science Literacy as Covariate - Mei Indra Jayanti; Muh Nasir; Umar Umar (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2026)
Critical thinking skills among elementary school students in Indonesia remain at a suboptimal level, as evidenced by the 2022 PISA science literacy score of 383, substantially below the OECD average of 485. Despite a growing body of research on Problem-Based Learning (PBL) in Indonesian science education, studies that statistically control for students' initial cognitive profiles when estimating PBL's effect on critical thinking remain scarce at the elementary level, limiting the precision and credibility of existing effect estimates. This study aimed to examine the effect of PBL on the critical thinking skills of fifth-grade students at SDN 33 Lampe, Bima City, Indonesia, with science literacy as a covariate. A quasi-experimental post-test only control group design was employed, with two classes selected through cluster random sampling and randomly assigned to conditions: Class V.A (n = 31) as the PBL group and Class V.B (n = 29) as the control group receiving conventional instruction. Science literacy data were obtained from a cognitive diagnostic assessment administered before the intervention as an independent covariate, while critical thinking was measured using a validated essay instrument covering six dimensions of Facione (2015). Data were analyzed using Analysis of Covariance (ANCOVA) with estimated marginal means reported for each group. Results indicated a highly significant effect of instructional model on critical thinking (F(1, 57) = 54.868, p < .001, partial η² = .490), with the PBL group obtaining an adjusted mean of 17.71 points higher than the control group after controlling for science literacy. Science literacy also demonstrated a significant covariate effect (partial η² = .178). Within the scope and constraints of this single-school study, PBL was associated with significantly higher critical thinking scores compared to conventional instruction.